2022
DOI: 10.3389/fonc.2022.903874
|View full text |Cite
|
Sign up to set email alerts
|

AXL Promotes Metformin-Induced Apoptosis Through Mediation of Autophagy by Activating ROS-AMPK-ULK1 Signaling in Human Esophageal Adenocarcinoma

Abstract: AXL receptor tyrosine kinase promotes an invasive phenotype and chemotherapy resistance in esophageal adenocarcinoma (EAC). AXL has been implicated in the regulation of autophagy, but the underlying molecular mechanism remains poorly understood. Herein, we investigate the mechanistic role of AXL in autophagy as well as metformin-induced effects on the growth and survival of EAC. We demonstrate that AXL mediates autophagic flux through activation of AMPK-ULK1 signaling in a reactive oxygen species (ROS)-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…The data from their study indicate that metformin-induced autophagy serves a pro-apoptotic function in EAC cells. Additionally, they substantiated the conclusion that the metformin-induced suppression of tumor growth in vivo is highly contingent on AXL expression, as demonstrated in a tumor xenograft mouse model of EAC [60]. The above are presented concisely in Table 5.…”
Section: Deciphering the Metformin's Influence On Apoptosis In Ecsupporting
confidence: 67%
See 3 more Smart Citations
“…The data from their study indicate that metformin-induced autophagy serves a pro-apoptotic function in EAC cells. Additionally, they substantiated the conclusion that the metformin-induced suppression of tumor growth in vivo is highly contingent on AXL expression, as demonstrated in a tumor xenograft mouse model of EAC [60]. The above are presented concisely in Table 5.…”
Section: Deciphering the Metformin's Influence On Apoptosis In Ecsupporting
confidence: 67%
“…Numerous studies have delved into the in vitro and in vivo consequences of metformin on ESCC and EAC cells, with predominant emphasis on two pathways: the signal transducer and activator of transcription 3 (Stat3)/Bcl-2 pathway [ 54 , 55 , 56 ] and the phosphoinositide 3-kinase (PI3K)/AKT/mTOR pathway [ 57 ]. Additionally, more recent studies have explored the anti-tumor activity of metformin through the modulation of redox homeostasis [ 58 , 59 , 60 ]. In relation to the former mechanism, studies have revealed that metformin demonstrates a selective inhibition of cell growth in ESCC tumor cells while sparing immortalized noncancerous esophageal epithelial cells.…”
Section: Understanding Metformin’s Molecular Mechanisms In Ecmentioning
confidence: 99%
See 2 more Smart Citations